Pengaruh tumpangsari kopi terhadap peningkatan pendapatan petani dataran tinggi Kabupaten Purbalingga Jawa Tengah - Bayu Mahendra; Aji Priambodo (Jurnal Agercolere, 2022)
This research aims to determine how much influence Arabica coffee intercropping has on increasing upland farmers' income. The object of this research is the Farmers Group by Raharja Mukti, located in Gunung Malang Hamlet, Serang Village, Karang Reja District, Purbalingga Regency, Central Java. The basis for choosing the location is because the location is right as the location where the Department of Agriculture distributes Arabica Coffee seeds and is also supported by the altitude of the location which is 1,400 meters above sea level. The number of samples in this study was 32 farmers and the sample selection was carried out by purposive sampling. The results of the normality test for each income of upland farmers who use the coffee intercropping system and those who do not are normally distributed. The analysis of this study shows that the lowest income for farmers who use the Arabica coffee intercropping system is IDR. 41,700,000 per year and the highest is IDR. 43,100,000. The average income of farmers with the intercropping system is IDR. 42,140,625 while the farmers who do not use the intercropping system are IDR. 40,418,750. There is a difference in the average income of farmers with the intercropping system and not IDR. 1,721,875, -. The t-test results show the value of Asymp. Sig. is 0.000 where the value is <0.05 so it can be said that the test of the average income of farmers with coffee intercropping and farmers not using intercropping is significant.